A review on gestational trophoblastic disease (Bangladesh Medical Journal, 2016)
Molar pregnancy occurs when the fertilization of the egg by the sperm goes wrong and leads to the growth of abnormal cells or clusters of water filled sacs inside the womb. This condition is one of a group of conditions known as gestational trophoblastic tumours (GTTs). Molar pregnancies used to be called hydatidiform mole but now most people call them molar pregnancies. Molar pregnancies are rare but they are the most common type of gestational trophoblastic tumour. In the UK, about 1 in 590 pregnancies is a molar pregnancy. In Asian women, molar pregnancies are about twice as common as in Caucasian women. Most molar pregnancies are benign. They can spread beyond the womb in some women, but are still curable. Molar pregnancies can either be complete or partial. In case of complete mole, no parts of foetal tissue are formed. In case of partial mole there may be some foetal tissue in the womb, alongside the molar tissue. By measuring the levels of ?hCG in blood and urine in high dilution helps to diagnose a molar pregnancy; an ultrasound scan can also diagnose many women with molar pregnancy. The molar tissue needs to be surgically removed. Afterwards, in around 10 to 15 out of 100 women, some molar tissue remains in the deeper tissues of the womb or other parts of the body. This is called a persistent gestational tumour. Invasive mole, choriocarcinoma, and placental site trophoblastic tumor (PSTT) termed as gestational trophoblastic neoplasia (GTN), which can progress, invade, metastasize, and lead to death if left untreated.These women need to have chemotherapy completely get rid of the abnormal cells.Bangladesh Med J. 2015 Jan; 44 (1): 51-56